Narratives of Violence and the Position of Victims in the Reporting of Israeli Attacks in Lebanon in Indonesian Media: Van Dijk's Analysis: - Luluk Zhuroida; Nazifatul Mardiah (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The Israeli-Palestinian conflict that spread to Lebanon reached its peak on November 18, 2025, when an Israeli airstrike hit the Ain Al-Hilweh refugee camp, killing 13 civilians. Reporting on international conflicts is never neutral, influenced by ideology, editorial interests, and the social context in which the media operates. This study aims to analyze the discourse construction of news coverage of the Israeli attack on the Palestinian refugee camp in Lebanon in Indonesian online media, namely INews.ID and Detik News. The study uses a qualitative-descriptive method with a Critical Discourse Analysis (CDA) approach modeled by Teun A. van Dijk, which includes analysis of text structure, social cognition, and social context. The research data consists of two online news texts published on November 19, 2023, and collected through documentation techniques using the listening and note-taking method. The results show that both media outlets raise the same theme, namely Israeli military aggression and its impact on civilian victims, but construct different discourse constructions. INews.ID tends to use evaluative and emotional diction that emphasizes the brutality of Israeli attacks, while Detik News presents a more informative and balanced discourse by contrasting Israel's claims and Hamas's rebuttals. This difference is clearly visible in the macrostructure (title selection), superstructure (writing scheme), and microstructure (use of active-passive sentences and diction). In conclusion, the discourse construction of both media is influenced by the social cognitive scheme and the social context of each media's editorial staff in representing international conflict.